The treatment of clinical depression in the context of marital distress. - Dessaulles, André. (University of Ottawa (Canada), 1991)
A total of 18 maritally-distressed couples, in which the female partner met diagnostic criteria for moderately severe clinical depression, were randomly assigned to Emotionally Focused Therapy (EFT) or to an individualized program of pharmacotherapy (PT) for the female partner. The purpose of the study was to examine the differential effectiveness of EFT, a systemic-experiential couple therapy, and PT in the prevention of relapse. Results suggest that both interventions were effective in reducing depression. Females in EFT were not depressed at follow-up but 2 females in PT did not respond to treatment. Marital adjustment increased significantly for females in EFT but not for their partners. The alleviation of depression in females in PT did not produce the hypothesized increase in their levels of marital adjustment, but their partners showed significant increases in their levels of marital adjustment. A differential pattern of relapse was not detected. Criteria for clinically-significant change suggest that females in EFT had better outcomes in terms of depression and marital distress, but that 2 couples in each group met the criteria of remitted depression and improvement in marital adjustment at 6-month follow-up. Results are discussed in light of an interpersonal approach to depression.
Keywords: Psychology, Clinical.